Informatics education practices and global relevance in madrasah in the Kurikulum Merdeka - Fathanah Hamidah Tsaqib (Hipkin Journal of Educational Research, 2025)
This study was motivated by the need to deepen understanding of how computer science is implemented in madrasahs within the Kurikulum Merdeka, while also addressing contemporary challenges through education relevant at the local, national, and global levels. This study holistically explores the practice of computer science education in madrasahs in the context of the Kurikulum Merdeka, which has thus far been focused more on public schools. The purpose of this study is to provide a comprehensive picture of how Informatics is taught in madrasahs and how its implementation can address contemporary challenges at the local, national, and global levels. This study uses a qualitative approach that applies the interview method in data collection. The results show that the curriculum is implemented in stages using a project-based learning approach that integrates Islamic values. The curriculum is developed in accordance with the policies of Kemendikbud and Kemenag, creating a unique learning experience that remains aligned with national objectives. Locally, the learning supports the character and needs of the surrounding community; nationally, it demonstrates the adaptation of cross-ministerial policies; and globally, it equips students with digital literacy and 21st-century competencies.   Abstrak Penelitian ini dilatarbelakangi oleh kebutuhan untuk memahami secara mendalam bagaimana mata pelajaran Informatika diimplementasikan di madrasah dalam konteks Kurikulum Merdeka, sekaligus menjawab tantangan zaman melalui pendidikan yang relevan secara lokal, nasional, dan global. Penelitian ini mengeksplorasi secara holistik praktik pembelajaran Informatika di madrasah dalam konteks Kurikulum Merdeka, yang selama ini lebih banyak difokuskan pada sekolah umum. Tujuan dari penelitian ini untuk memperoleh gambaran yang komprehensif mengenai bagaimana Informatika diajarkan di madrasah serta bagaimana pelaksanaannya dapat menjawab tantangan zaman baik secara lokal, nasional, maupun global. Penelitian ini menggunakan pendekatan kualitatif yang menerapkan metode wawancara dalam pengumpulan data. Hasil penelitian menunjukkan bahwa implementasi kurikulum dilakukan secara bertahap dengan pendekatan pembelajaran berbasis proyek yang mengintegrasikan nilai keislaman. Kurikulum disusun berdasarkan kebijakan Kemendikbud dan Kemenag, menciptakan pembelajaran yang khas namun tetap selaras dengan tujuan nasional. Secara lokal, pembelajaran mendukung karakter dan kebutuhan komunitas sekitar; secara nasional menunjukkan adaptasi kebijakan lintas kementerian; dan secara global, membekali murid dengan literasi digital dan kompetensi abad ke-21. Kata Kunci: Informatika; Kurikulum Merdeka; madrasah; sejarah Informatika